An Analysis of Graduate Unemployment Duration: The Case of Universiti Utara Malaysia - Tuan Rohasnida, Tuan Teh (2011)
The persistent of unemployment rate among the graduates in Malaysia are a worrying trend. One of reasons of Malaysian graduates face difficulties to find jobs is labor market changes are too rapidly and competitively. The government should look for new initiatives to reduce graduate unemployment to reduce the waste of education and training investment. There is no doubt, a large number of studies have been made in analyzing the factors influencing the graduate unemployment in Malaysia. However, it is only a few of them focus on the duration of unemployment which is one of the important aspects in view the seriousness of unemployment problem. Therefore, this thesis aims to fill this research gap. This thesis is intended to provide understanding and a clear picture of the actual situation of unemployed graduates in the country, particularly for policy makers. With cross-section data of 441 graduates of Universiti Utara Malaysia (UUM), various methodologies are used: descriptive, correlation and Multiple Regression Model. Results of this thesis indicate that the types of degrees, ethnic group, the family background and CGPA are the significant determinant of graduate’s unemployment duration. It is also found that the mean unemployment duration of graduates are less than three months and hence, the problem of graduate unemployment might not as serious as suggested by the incident of unemployment (which is reported to be around 25% ). Based on the main findings, policies and theoritical implications are suggested.